2018
DOI: 10.5946/ce.2018.186
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Narrow-Band Imaging in Endoscopic Submucosal Dissection of the Stomach

Abstract: There have been many advances in endoscopic imaging technologies. Magnifying endoscopy with narrow-band imaging is an innovative optical technology that enables the precise discrimination of structural changes on the mucosal surface. Several studies have demonstrated its usefulness and superiority for tumor detection and differential diagnosis in the stomach as compared with conventional endoscopy. Furthermore, magnifying endoscopy with narrow-band imaging has the potential to predict the invasion depth and tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Although this new pCLE classification system correlates well with specific histological conditions and has been reproducible by multiple investigators, it is inferior to the Updated Sydney system for the diagnosis of atrophic gastritis. Additional studies have cultivated its use for tumor differential detection in the stomach and esophagus by combination with endoscopic submucosal dissection, and it has demonstrated efficacy for the treatment of neoplasms[ 17 , 18 ]. In our study, we compared the Updated Sydney system and the Kimura-Takemoto visual endoscopic classification system for atrophic gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Although this new pCLE classification system correlates well with specific histological conditions and has been reproducible by multiple investigators, it is inferior to the Updated Sydney system for the diagnosis of atrophic gastritis. Additional studies have cultivated its use for tumor differential detection in the stomach and esophagus by combination with endoscopic submucosal dissection, and it has demonstrated efficacy for the treatment of neoplasms[ 17 , 18 ]. In our study, we compared the Updated Sydney system and the Kimura-Takemoto visual endoscopic classification system for atrophic gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the diagnosis of H pylori infection with WLI showed low sensitivity and poor interobserver agreement [ 11 , 32 - 34 ]. However, studies with IEE commonly showed increased diagnostic accuracy of premalignant or malignant lesions during endoscopic examination [ 11 , 12 ]. Previous studies with IEE also indicated the usefulness of LCI for the diagnosis of H pylori infection [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Image-enhanced endoscopy (IEE), such as narrow-band imaging (NBI), BLI, or linked color imaging (LCI), with or without magnification, has been developed. Previous studies have indicated increased diagnostic accuracy of gastrointestinal neoplasms with the application of these modalities during endoscopic examination [ 11 , 12 ]. This also requires considerable training and prolonged procedure time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are some limitations when using ME‐NBI in clinical practice. First of all, considerable training and experience with endoscope manipulation and interpretation of images are required for optimal performance of ME‐NBI 11,34 . However, the newly developed DF endoscope (GIF‐HQ290; Olympus) compensates for the shortcomings of conventional magnification endoscopes and NBI systems.…”
Section: Discussionmentioning
confidence: 99%